Primer for Experimental Methods in Organization Theory - Levine, Sheen S.; Schilke, Oliver; Kacperczyk, Olenka; Zucker, Lynne G. (Organization Science, 2023)
Experiments have long played a crucial role in various scientific disciplines and have been gaining ground in organization theory, where they add unique value by establishing causality and uncovering theoretical mechanisms. This essay provides an overview of the merits and procedures of the experimental methodology, with an emphasis on its application to organization theory. Drawing on the historical roots of experiments and their impact across science, we argue the method holds immense potential for furthering organization theory. We highlight key advantages of experimental methods, including high internal and construct validity, vividness in communicating findings, the capacity to examine complex and understudied phenomena, and the identification of microfoundations and theoretical mechanisms. We alleviate some concerns about external validity and offer guidance for designing and conducting sound, reproducible experimental research. Ultimately, we contend that the current experimental turn holds the potential to reorient organization theory. History: This paper has been accepted for the Organization Science Special Issue on Experiments in Organizational Theory. Funding: This work was supported by the Otto Moensted Foundation, which granted the Otto Moensted Visiting Professorship to S. S. Levine, and a National Science Foundation CAREER Award from the Directorate for Social, Behavioral and Economic Sciences [Grant 1943688] to O. Schilke. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2023.18093 .